ENGLISH AND KARAKALPAK COLOUR IDIOMS AND THEIR CLASSIFICTIONS - Dilfuza Gaipova (Journals Park Publishing, 2022)
This study provides  the usage, classification of Colour idioms in comparative ways illustrating with the examples. The most common colour idiom such as black is defined with a wide range of concepts along with structure.
Keywords: idioms, phrasalogical units, figurative meaning, Kirk-Kiz, phrasalogism, black labour.